Evolution of Pliocene-Pleistocene tropical terrestrial Andean temperature amplification - Lina C. Pérez-Angel; Julio Sepúlveda; Peter Molnar; Héctor Mora-Paez; Angélica Parrado; Katelyn Eaman; James Russell; Balaji Rajagopalan; Catalina González-Arango; Kathryn Snell; Camilo Montes; James L. Crowley; et al. (Proceedings of the National Academy of Sciences, 2026)
The Pliocene is the most recent epoch in which the Earth warmed under atmospheric CO 2 levels similar to today (>400 ppm). The Pliocene then transitioned to the colder Pleistocene epoch, with the initiation of large-scale Northern Hemisphere glaciations. Although ocean temperature changes across these epochs are relatively well-known, quantitative estimates of the magnitude of land temperature change in the tropics are scarce. We provide a Plio-Quaternary quantitative air temperature record based on the distribution of bacterial branched glycerol dialkyl glycerol tetraethers (brGDGTs) preserved in sediments of the Funza-II core in the Sabana de Bogotá, Colombia (~4°N). Using a refined age model based on new U-Pb zircon dates from ash layers, and a novel mixed-source model that disentangles contributions from lake- and soil-derived brGDGTs, we show that warm Pliocene (3.8 to 2.58 Ma) temperatures were 4 . 8 - 1.4 + 1.8 °C warmer than the last ~800,000 y of the colder Pleistocene. The evolution of Pliocene-Pleistocene temperature in our record largely mirrors long-term tropical sea surface temperature (SST) cooling, highlighting the linkages between sea and land temperatures in the low latitudes via greenhouse-gas forcing. The median amplitude of Pliocene-Pleistocene cooling in the northern tropical Andes exceeds that predicted by theory, highlighting the importance of regional feedbacks including lapse rate adjustments and/or changes in Pacific SST gradients to the long-term evolution of Andean temperature. This first quantitative terrestrial temperature reconstruction within 5° of the equator over the past 3.8 My highlights that both regional and global processes must be considered when constraining uncertainties for future warming scenarios.